Integration of lean and agile approaches in supply chain management - Obora, Hubert (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The purpose of this chapter is to present the possibilities of integrating lean and agile approaches in supply chain management. At the beginning, the concepts of supply chain and supply chain management were characterized. Next, the approaches to supply chain management that are present in the literature are presented with a special focus on Lean Suppluy Chain and Agile Supply Chain. The characteristics of the two approaches have given an indication of the basic differences between them and the possibility of integrating them for supply chain management purposes. The text ends with an indication of how to integrate lean and agile approaches in supply chain management.